Froth flotation of ilmenite by using the dendritic surfactant 2-decanoylamino-pentanedioic acid. (1st May 2021) - Deng, Lanqing; Zhu, Liangdi; Fei, Lingyun; Ma, Xin; Deng, Fang; Zuo, Rui; Huang, Zhiqiang; Li, Liqing; Xie, Yuexiang; Xiao, Zhihong; Liu, Rukuan
Highlights: 2-decanoylamino-pentanedioic acid was first introduced as collector. DPA exhibited superior affinity to ilmenite. DPA owned two unique hydrophobic groups and three hydrophilic groups. Abstract: In this work, 2-decanoylamino-pentanedioic acid (DPA), a novel dendritic surfactant, was designed, synthesized, and exploited as a collector for the flotation of ilmenite. The experimental froth flotation results illustrated that DPA had a superior collecting activity, adsorbed better on the ilmenite surface than oleic acid, and could effectively recover ilmenite from titanomagnetite at a pH of approximately 7. DPA's unique properties, including two hydrophobic groups and three hydrophilic groups, allowed it to coat the ilmenite surface, rendering it a superior collector.